Feasibility of Surgeon-Delivered Audit and Feedback Incorporating Peer Surgical Coaching to Reduce Fistula Incidence following Cleft Palate Repair: A Pilot Trial. Issue 1 (July 2020) - Sitzman, Thomas J.; Tse, Raymond W.; Allori, Alexander C.; Fisher, David M.; Samson, Thomas D.; Beals, Stephen P.; Matic, Damir B.; Marcus, Jeffrey R.; Grossoehme, Daniel H.; Britto, Maria T.
Abstract : Background: Improving surgeons' technical performance may reduce their frequency of postoperative complications. The authors conducted a pilot trial to evaluate the feasibility of a surgeon-delivered audit and feedback intervention incorporating peer surgical coaching on technical performance among surgeons performing cleft palate repair, in advance of a future effectiveness trial. Methods: A nonrandomized, two-arm, unblinded pilot trial enrolled surgeons performing cleft palate repair. Participants completed a baseline audit of fistula incidence. Participants with a fistula incidence above the median were allocated to an intensive feedback intervention that included selecting a peer surgical coach, observing the coach perform palate repair, reviewing operative video of their own surgical technique with the coach, and proposing and implementing changes in their technique. All others were allocated to simple feedback (receiving audit results). Outcomes assessed were proportion of surgeons completing the baseline audit, disclosing their fistula incidence to peers, and completing the feedback intervention. Results: Seven surgeons enrolled in the trial. All seven completed the baseline audit and disclosed their fistula incidence to other participants. The median baseline fistula incidence was 0.4 percent (range, 0 to 10.5 percent). Two surgeons were unable to receive the feedback intervention. Of the five remaining surgeons, two were allocated to intensive feedback and three to simple feedback. All surgeons completed their assigned feedback intervention. Among surgeons receiving intensive feedback, fistula incidence was 5.9 percent at baseline and 0.0 percent following feedback (adjusted OR, 0.98; 95 percent CI, 0.44 to 2.17). Conclusion: Surgeon-delivered audit and feedback incorporating peer coaching on technical performance was feasible for surgeons.